2009
DOI: 10.4104/pcrj.2009.00038
|View full text |Cite
|
Sign up to set email alerts
|

Technology and its role in respiratory care

Abstract: Introduction: Telemonitoring, telemedicine, clinical and medical informatics or telecare, are terms used to describe the use of technology along with local clinical protocols to monitor remotely a patient's medical condition in their own home. In respiratory medicine, where large numbers of people have long term conditions such as asthma and chronic obstructive pulmonary disease (COPD), the role of such monitoring technology in the management of patients is of great interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 47 publications
(50 reference statements)
1
32
0
3
Order By: Relevance
“…2,3 The present study has identified an area for quality improvement by providing strong evidence that the aspect ratio affects the visual interpretation of relatively acute changes in biological data such as during asthma exacerbations. The findings have immediate relevance to health monitoring, where the aim is to improve outcomes by early identification of deterioration.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…2,3 The present study has identified an area for quality improvement by providing strong evidence that the aspect ratio affects the visual interpretation of relatively acute changes in biological data such as during asthma exacerbations. The findings have immediate relevance to health monitoring, where the aim is to improve outcomes by early identification of deterioration.…”
Section: Discussionmentioning
confidence: 84%
“…With increasing use of internet and mobile phone-based resources for telehealth monitoring, [1][2][3] the visual display of data is also becoming more common. Charts may be used to confirm clinical diagnoses, to increase patient awareness of their condition, or to provide early warning of deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…Current use of telehealth technologies in respiratory medicine is limited; 2 evidence for their effective use is accruing, [8][9][10][11][12][13][14][15][16][17][18][19] but there remain concerns about clinical and cost effectiveness. 7,17 These issues will be affected by the setting in which telehealth is deployed.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, while recent articles have discussed the potential for telehealth in respiratory disease, they have also pointed out a lack of published robust evidence of clinical and economic benefit. 2,6,7 The feasibility of telecare and telemonitoring for COPD and asthma has been demonstrated, [8][9][10][11][12] and telemonitoring has been reported to reduce hospital admissions, emergency department visits and length of stay. 13,14 Remote monitoring of chemotherapy by mobile phone has also proven successful in lung cancer management.…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary rehabilitation should be a core component of COPD management and should be associated with effective pharmacological therapy [1,42]. Telehealth (the utilisation of telecommunication technology for the transfer of health-related services and information) and remote patient monitoring are ideally suited for patients with COPD, but the benefits need to be evaluated in larger, appropriately controlled clinical studies [43].…”
Section: Copd and Asthma: Differential Diagnosis And Overlap Syndromementioning
confidence: 99%